Whose mission, whose orders? : British civil-military command and control in Northern Ireland, 1968-1974 - Charters, David A., 1949- (desLibris. Books collection., 2017)
"Who ran the war in Northern Ireland--the politicians or the generals? This book presents evidence that the answer is: neither--by themselves. Utilizing scholarly secondary sources on the Troubles as well as official records held at the National Archives at Kew and the Public Record Office of Northern Ireland, the author examines the two-way process of consultation between government and military officials that tasked the military with turning political objectives into viable military operations. By presenting six case studies of key events from 1968-1974, the author illustrates the complex and dynamic balance of civil-military objectives that informed security policy and operations during the conflict."--